DOES DIVIDEND POLICY MEDIATE THE EFFECT OF FINANCIAL PERFORMANCE AND CAPITAL STRUCTURE ON FIRM VALUE? - Reza Septiana Wibowo; Tarsisius Renald Suganda; Daniel Sugama Stephanus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
A company's dividend policy is a crucial element that influences financial performance and capital structure on firm value. This study builds on earlier research by analyzing the function of dividend policy as a mediator between financial performance, capital structure and firm value, with a focus on stocks included in the ISSI Index. This research aims to examine whether dividend policy serves as a mediating variable in the relationship between financial performance, capital structure and firm value among manufacturing firms listed on the ISSI Index. This quantitative study utilized a sample of 425 observations from manufacturing companies on the ISSI Index during the 2019–2023 period. The PLS-SEM position was employed in regression analysis. Profitability (ROA), liquidity (CR), leverage (DER), and capital structure (DAR) seemed amid the independent variables this were studied. Firm value was measured by Tobin’s Q and PBV as dependent variables, while dividend policy (DPR) served as the mediating variable. It was found that profitability and capital structure contribute positively to firm value, as measured by Tobin’s Q and PBV, whereas liquidity has a negative impact. Leverage only affects firm value when PBV is used as a proxy. Also, this study demonstrates that the relationship between profitability, liquidity, leverage, and capital structure on firm value (Tobin’s Q and PBV) is significantly mediated by dividend policy. By strengthening and extending the bird-in-the-hand theory, this research offers a theoretical contribution by highlighting the importance of dividend payouts in enhancing firm value, particularly for manufacturing companies listed on the ISSI Index.